Marketing mix and factors that affect cigarette consumption - Hardiyono, Tommy; Siswadi, Bambang; Machfudz, Masyhuri (Journal of Agricultural Socio-Economics (JASE), 2020)
The Ministry of Industry noted the number of workers in the industrial sector was 5.98 million people, higher than the number of manufacturing and distribution (4.28 million), and the rest belonged (1.7 million). The purpose of this study is to analyze the marketing mix and the factors that influence the consumption of cigarettes. The research data consisted of primary data obtained through direct interviews with consumers, taken by accident sampling with a total sample of 95 respondents. Data analysis uses multiple linear regression models. The results showed that the product in the form of product availability contributed to cigarette consumption by 50.52%, the price in the form of a price ratio of 45.26%, the distribution variable in the form of ease in getting products by 47.36%, and promotion in the form of advertising attractiveness by 46, 31%. Price, distribution, and promotion have a significant effect on cigarette consumption, while products do not affect. It is necessary to improve the quality of packaging, physical form, and taste with a balanced price